Pengembangan Instrumen Penilaian Sikap Peserta Didik Pada Pembelajaran Kimia Dengan Teknik Peer-Assessment - Asbupel, Fatnan; Angela, Lia; Alfian, Muhammad (CV. ITTC INDONESIA, 2024)
This research aims to produce an instrument for assessing students' attitudes towards chemistry learning using peer assessment techniques. The research method is R&D using the ADDIE development model. The research subjects were State High School students in Sleman Regency, consisting of 17 State High Schools in Sleman Regency. The sampling technique is a simple random sampling technique with data analysis using Structural Equation Modeling (SEM). The research results show that the resulting instrument has a construct in the form of an I-P Scale with a choice of 5 answer choices. The instrument contains 31 questions which are divided into 8 aspects of attitude, namely curiosity, objectivity, critical thinking, perseverance, thoroughness, openness, and cooperation, responsibility, and care for the environment. The instrument for assessing students' attitudes in chemistry learning in the form of peer assessment has reliability and is effectively used in assessing attitudes in chemistry learning.